Papel da 5-lipoxigenase em modelo experimental de infecção pulmonar pelo fungo patogênico Paracoccidioides brasiliensis - Patricia Campi Santos (2011)
Paracoccidioidomycosis is a human chronic granulomatous disease caused by the dimorphic fungus Paracoccidioides brasiliensis, which affects predominantly adult males. It is the most prevalent mycosis in Latin America, occurring primarily in Brazil, Colombia and Venezuela. Natural infection occurs by inhalation of conidia present in the environment, and lungs are the main organ involved. PCM presents a broad spectrum of clinical manifestations, and disease severity is related to the pattern of host immune response. Leukotrienes are inflammatory mediators derived from arachidonic acid metabolism via the enzyme 5-lipoxygenase (5-LO). They are described as chemotactic agents and regulators of the antimicrobial activity of innate immune cells, and protective role against different microbial agents. However, there is an absence of data regarding to the role of the enzyme and its products in PCM. In this study, we evaluated the role of the enzyme 5-lipoxygenase in regulating the immune response after infection with P. brasiliensis in vivo and in vitro. Using wild-type (WT) and 5-LO-deficient mice (5-LO-/-) infected with P. brasiliensis, we evaluated the following immunological parameters in vivo: lethality, cellular infiltration, fungal load, myeloperoxidase activity (MPO) and cytokine production. In vitro, we used pharmacological tools to assess phagocytosis, fungicidal activity, and concentration of nitric oxide (NO) and reactive oxygen species (ROS) after infection of macrophages with yeast cells of P. brasiliensis. The results show that the absence of 5-LO resulted in the death of 100% of animals. Furthermore, infection of 5-LO-/- mice with P. brasiliensis resulted in elevated concentration of pro-inflammatory cytokines (TNF-, IL-1 and IL-6) and chemokines (CXCL-1/KC and CXCL-2/MIP-2); imbalance in the recruitment of neutrophils, increased MPO activity and fungal proliferation in the lungs when compared to WT mice. In vitro, were observed a decreased phagocytosis and fungicidal activity of macrophages treated with 5-LO inhibitor and infected with yeasts of P. brasiliensis. Also, was observed decreased concentration of NO and ROS after treatment of macrophages with inhibitors of 5-LO and antagonists of 5-LO metabolic products. Thus, the production of lipid mediators by the enzyme 5-lipoxygenase may play a role in the effector mechanisms of the immune response and in host defense against P. brasiliensis infection.